Virtual Reality Prototype Development for Structural Learning in Bridge Engineering - Muhammad Fauzan Nuri Misbahhuddin; Faqih Ma'arif; Galeh Nur Indriatno Putra Pratama; Moch. Bruri Triyono; Dina Adinda (Universitas Negeri Yogyakarta, 2026)
Background: The advancement of immersive technology such as Virtual Reality (VR) provides an opportunity to improve civil engineering learning by offering interactive 3D environments that support structural exploration. However, learning media based on VR for bridge engineering is still rarely developed and optimized in the academic field. This condition indicates the need for interactive digital media that strengthens conceptual understanding, spatial visualization, and practical interpretation of bridge structures. Methods: This research employed a development approach using the 4D model (Define, Design, Develop, and Disseminate, limited only to the Develop stage). Evaluation was conducted through expert review involving material and media assessors to refine visual quality, navigation flow, and content presentation. Results: The result of the development process is a functional VR prototype that allows users to explore bridge structures interactively. Users can observe components such as abutments, piers, girders, decks, and foundations from multiple perspectives, supported by information pop-ups that describe structural function and material characteristics. Expert feedback indicated that VR media has strong potential to enhance understanding of structural behavior and spatial configuration, and is considered feasible to be continued into the testing stage. Revisions focused on improving text readability, navigation control, texture sharpness, and instructional clarity. Conclusion: The study demonstrates that VR-based learning media can serve as an innovative tool for bridge construction learning by bridging theoretical concepts with immersive visualization. The product developed in this study is ready for further implementation and effectiveness testing to evaluate student response and learning outcomes.